PENINGKATAN AKTIVITAS SISWA MELALUI PEMBELAJARAN KOOPERATIF DISERTAI METODE OUTDOOR LEARNING PADA MATERI KELANGSUNGAN HIDUP DI KELAS IX A SMPN 1 SAMALANTAN - Suhaimi, Suhaimi; Yokhebed, Yokhebed (Universitas Tanjungpura, 2014)
This research was aimed to improve students' learning activities through cooperative learning model with outdoor learning method at viability organisms on IX A Junior Secondary School 01 Samalantan. Subjects in this study 33 students. The research instrument used is the observation sheet and field notes. Results showed that an increase in activity after the students are given cooperative learning model with outdoor learning method. Based on the analysis of data obtained the increased activity of the students at 72,73% after implementation cooperative learning model with outdoor learning method in two cycles of action. Keywords: Students’ activities, cooperative learning, outdoor learning method.